KARAKTERISTIK HUKUM ISLAM - Hendra Gunawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
The term Islamic law is an official term in Indonesia, because in Arabic literature included in the al-Qur'an and Sunnah is actually not known as an Islamic legal term in a series of words. However, these two words can be separately found in Islamic sharia and fiqh. The scholars identify Islamic law with fiqh, at least in understanding Islamic law must first understand fiqh. Islamic law has differences with other laws, both from the source and the object, because Islamic law has two legal objects that regulate human relations with Allah SWT which is called worship and regulate the relationship between fellow humans and the universe called muamalah. Whereas, the general law of the object only regulates the relationship between fellow human beings in community life, besides that in this article the author wants to describe the characteristics or characteristics that Islamic law has.